The Influence of Social Environment, Individual Characteristics and Psychological Processes on Congregation Preferences in Choosing a Mosque for Prayer - Muhammad Hasan, Hamid (Happiness: Journal of Psychology and Islamic Science, 2026)
Mosques serve not only as places of worship but also as centers for spiritual and social development for Muslims. In the context of dynamic urban communities, worshippers have specific preferences when choosing a mosque for prayer. This study aims to determine the influence of the social environment, individual characteristics, and psychological processes on worshippers' preferences in choosing a mosque for prayer. This study used a quantitative approach with a survey method using a questionnaire as the primary data source. The study was conducted in Denpasar Bali, with respondents from mosque worshippers selected purposively, where the number of sample used was 340 respondents. Data analysis was performed using the Partial Least Squares (PLS) method with the assistance of SmartPLS 4.0 software. The results show that individual characteristics have a positive and significant influence on worshippers' preferences in choosing a mosque a path coefficient of 0.272 with a t-value of 2.198. Psychological processes also have a positive and significant influence on worshippers' preferences a path coefficient of 0.368 with a t-value of 2.767. Meanwhile, the social environment has a negative and insignificant influence on worshippers' preferences in choosing a mosque a path coefficient of -0.026 with a t-value of 0.230. These findings indicate that congregant preferences are more determined by individual internal factors and psychological experiences than by surrounding social factors. This research provides important implications for mosque managers to emphasize strengthening the individual and psychological aspects of congregants in an effort to increase comfort, loyalty, and participation.